2018
DOI: 10.1016/j.jcf.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of humoral immune response against Pseudomonas aeruginosa biofilm infection in cystic fibrosis

Abstract: P. aeruginosa chronic lung infection is the major cause of morbidity and mortality in patients with cystic fibrosis (CF), and is characterized by a biofilm mode of growth, increased levels of specific IgG antibodies and immune complex formation. However, despite being designed to combat this infection, such elevated humoral response is not associated with clinical improvement, pointing to a lack of anti-pseudomonas effectiveness. The mode of action of specific antibodies, as well as their structural features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 77 publications
0
41
0
4
Order By: Relevance
“…Infection of the CF airway with Pa starts with planktonic (free living), variants often originating from the environment. Over time, as bacteria adapt to the CF airway, they environment, they form a biofilm (98). In this section we address the contribution of Pf phages to Pa biofilm formation and to other phenotypes involved in Pa pathogenicity.…”
Section: Pf Effects On Pa Phenotypes and Fitnessmentioning
confidence: 99%
“…Infection of the CF airway with Pa starts with planktonic (free living), variants often originating from the environment. Over time, as bacteria adapt to the CF airway, they environment, they form a biofilm (98). In this section we address the contribution of Pf phages to Pa biofilm formation and to other phenotypes involved in Pa pathogenicity.…”
Section: Pf Effects On Pa Phenotypes and Fitnessmentioning
confidence: 99%
“…It has been reported that swarming motility is essential for biofilm development (Shrout et al, ). Moreover, the biofilm mode of growth is proposed to occur in the lungs of chronically P. aeruginosa ‐infected cystic fibrosis patients and bacterial cells are thus protected from antibiotic treatment and the immune response (Høiby et al, ; Mauch, Jensen, Moser, Levy, & Hoiby, ). The antimicrobial effects of Asian ginseng, American ginseng, and notoginseng and the possible underlying mechanisms are summarized in Table .…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…A vicious cycle of persistent inflammation and infections affects severely the pulmonary parenchyma (Nichols and Chmiel, 2015). The main respiratory pathogens found in CF patients are Pseudomonas aeruginosa (Hoiby, 2011;Mauch et al, 2018), Staphylococcus aureus (Schwerdt et al, 2018;Wong et al, 2013), and Burkholderia cepacia (Regan and Bhatt, 2016). Eventually lung transplantation is needed for CF patients with end-stage lung disease (Snell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%